The Influence Of Motivation And Work Environment On Employee Productivity Of The Tirta Hidayah Regional Public Company (Perumda) Of Bengkulu City - Romi Tabuma; Islamuddin (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
A good organization is an organization that seeks to improve the capabilities of its human resources, because this is a key factor for increasing employee work productivity. The purpose of this study was to determine the effect of motivation and work environment on the productivity of employees of the Tirta Hidayah Regional Public Company, Bengkulu City.This research can be classified as causal associative quantitative research. Respondents are permanent employees at the Tirta Hidayah Regional Public Company, Bengkulu City. Data were collected through questionnaires and data analysis using multiple linear regression models and processed with SPSS software.The results showed that work motivation had an effect on the work productivity of employees of the Tirta Hidayah Regional Public Company, Bengkulu City t_count (3.320) > t_table (1.986). This explains that the higher the employee's work motivation, the higher the work productivity will be. The work environment influences the work productivity of employees of the Tirta Hidayah Regional Public Company, Bengkulu City t_count (6.017) > t_tabel (1.986). This explains that the better the work environment, the higher work productivity will be. Work motivation and work environment influence the work productivity of employees of the Tirta Hidayah Regional Public Company, Bengkulu City F_count (67.122) > F_count (19.485). This explains that the higher the employee's work motivation and the better the work environment, the higher the work productivity will be.